2017
DOI: 10.1002/wsb.762
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for evaluation and treatment of lead poisoning of wild raptors

Abstract: Lead poisoning is a threat to birds, particularly scavenging birds of prey. With the availability of portable lead-testing kits, an increasing number of field researchers are testing wild-caught birds, in situ, for lead poisoning. We describe guidelines for evaluation of lead toxicity in wild raptors by outlining field testing of blood-lead concentrations, presenting criteria for removing a lead-poisoned bird from the wild for treatment, and suggesting strategies for effective treatment of lead intoxicated rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
1
22
0
5
Order By: Relevance
“…Using the threshold of 10 mg/dL described for background BLLs in raptors (Redig and Arent 2008;Langner et al 2015;Fallon et al 2017), we found that the LCII measurements correlate better with those of the ICP-MS in the series of animals with BLLs >10 mg/dL (which includes all of the griffon vultures examined in the present study) than in those with background BLLs (Figure 4). Using the threshold of 10 mg/dL described for background BLLs in raptors (Redig and Arent 2008;Langner et al 2015;Fallon et al 2017), we found that the LCII measurements correlate better with those of the ICP-MS in the series of animals with BLLs >10 mg/dL (which includes all of the griffon vultures examined in the present study) than in those with background BLLs (Figure 4).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Using the threshold of 10 mg/dL described for background BLLs in raptors (Redig and Arent 2008;Langner et al 2015;Fallon et al 2017), we found that the LCII measurements correlate better with those of the ICP-MS in the series of animals with BLLs >10 mg/dL (which includes all of the griffon vultures examined in the present study) than in those with background BLLs (Figure 4). Using the threshold of 10 mg/dL described for background BLLs in raptors (Redig and Arent 2008;Langner et al 2015;Fallon et al 2017), we found that the LCII measurements correlate better with those of the ICP-MS in the series of animals with BLLs >10 mg/dL (which includes all of the griffon vultures examined in the present study) than in those with background BLLs (Figure 4).…”
Section: Resultsmentioning
confidence: 52%
“…On the other hand, we considered the threshold of 10 mg/dL, which has been proposed as a limit at which a raptor can be considered to have high levels of Pb, probably with pathological consequences (Redig and Arent 2008;Fallon et al 2017). We considered 2 different thresholds for this.…”
Section: Statistical Analyses and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 44% (n ¼ 31) of the sample concentrations were <LOD (Table 1), 15% (n ¼ 10) of the bald eagle blood samples were above the threshold for background blood lead concentrations (10 mg/dL), and 2 of the bald eagles had blood lead concentrations above the threshold for clinical poisoning (40 mg/dL; Pokras and Kneeland 2008;Fallon et al 2017). A total of 44% (n ¼ 31) of the sample concentrations were <LOD (Table 1), 15% (n ¼ 10) of the bald eagle blood samples were above the threshold for background blood lead concentrations (10 mg/dL), and 2 of the bald eagles had blood lead concentrations above the threshold for clinical poisoning (40 mg/dL; Pokras and Kneeland 2008;Fallon et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We tested blood lead concentrations of 244 osprey including 47 breeding adults ( (n ¼ 92) of the osprey blood samples fell below the LODs (Table 1), 3% (n ¼ 7) of the osprey blood samples were above the threshold for background blood lead concentrations (10 mg/dL), and none of the osprey had blood lead concentrations above the threshold for clinical poisoning (40 mg/dL; Pokras and Kneeland 2008;Fallon et al 2017). There was no statistical difference in the detection frequency (p ¼ 0.84, x 2 ¼ 0.04, df ¼ 1) or lead concentrations (p ¼ 0.92, x 2 ¼ 0.01, df ¼1, note that both the chisquare test for detection frequency and the modified Wilcoxon test for concentrations produce a x 2 statistic) between adult and nestling osprey.…”
Section: Age-and Region-specific Lead Exposure Of Osprey and Bald Eaglesmentioning
confidence: 99%